Takeover of the National Prosecutor’s Office - Golec, Andrzej (Finding a way out of Poland's rule-of-law crisis: Possible courses of action and reform, 2026)
On January 12, 2024, Minister of Justice Adam Bodnar handed Dariusz Barski a document declaring that his appointment as National Prosecutor had been unlawful. Prime Minister Tusk subsequently entrusted the duties of National Prosecutor to Jacek Bilewicz, and shortly thereafter appointed Dariusz Korneluk to the position — both actions taken in violation of the applicable procedure requiring the consent of the President of the Republic of Poland.Both the Supreme Court and the Constitutional Tribunal confirmed that Dariusz Barski remained the lawful National Prosecutor, and that the actions of Bilewicz and Korneluk were legally ineffective. All appointments and dismissals of prosecutors carried out by them must be treated as non-existent. However, procedural actions taken by prosecutors who acted in good faith should not be automatically invalidated.Dariusz Barski should return to his position without delay. Looking further ahead, the author advocates for the constitutionalization of the prosecution service and for vesting either the President of the Republic of Poland or the general public — through direct elections — with the authority to appoint the Prosecutor General.